Standard operating procedures and regulatory guidelines : blood banking - Saluja, GP; GL, Singal (India: Jaypee Brothers Medical Publishers, 2014)
This book has been designed to provide blood bank technicians, students undergoing various courses in medical technology, blood bank specialists and residents with a concise and thorough practical and simple procedural guide to all the procedures to check the quality and safety of the blood donated for transfusion.
Section1. Standard Operating Procedures 1. Standard operating procedure for preparing, revising and using Standard Procedures 2. Criteria for the Donor Selection 3. Donor Screening 4. Donor Screening for Hemoglobin 5. Estimation of Hemoglobin of the Donor 6. Estimation of Hemoglobin by Hemo-Control 7. Preparation of Phlebotomy Site 8. Selection of the blood bags 9. Venipuncture and blood collection Section2. Regulatory Guidelines 2.1 Regulatory requirements of blood and / or Its components including blood products 2.2 Drugs and Cosmetics rules 2.3 Schedule F under the drugs and cosmetics rules 1945 2.4 Storage conditions, expiry of blood , blood components and blood products
Keywords: HEMATOLOGÍA; HEMATOLOGY; TRANSFUSIÓN DE SANGRE; BANCOS DE SANGRE